Propuesta de producto turístico para COOPROTURS R.L de San Ramón, La Virgen, Sarapiquí - Calvo-Quirós, Angeline (Instituto Tecnológico de Costa Rica, 2016)
This paper is a touristic product design for Multiple Services and Tourism Cooperative of San Ramón, La Virgen, Sarapiquí (COOPROTURS R.L.). It's divided in three objectives: to identify available resources at attractions, plant, infrastructure and superstructure level in San Ramón community, to determine the components that will form up the touristic product proposal of the cooperative and to define the appropriate methodology for the touristic product design of the cooperative. COOPROTURS R.L. was created in 2015, composed of thirty six partners, distinguished by proactivity and coordination, as about five more committees working for the welfare of the people. This cooperative is focus on strengthen sales of their partner’s products, from stevia to agriculture products and cattle raising, equally interested in making rural tourism part of its production activities through the conservation of natural resources and heritage. San Ramón, Sarapiquí is site with lush natural, cultural and rural wealth, so this study focuses on demonstrate the potential and contribute with a proposal to allow the cooperative to have a baseline to guide its planning and distribution of its products (goods, services and activities) that could form a rural tourism product. Resulting in an analysis of the tourism heritage, this show that the plant and infraestructure identified in the community have basic conditionsand must improve, there is support from both governmental and private institutions, and much potential natural, cultural and rural level, all it validated a workshop with COOPROTURS R.L. Concluded in an eight services proposal that could compose the touristic product of the cooperative: tour opperator, transportation, food, lodging, guided tour service, San Ramón, Sarapiquí tours, natural watering place and souvenir. This coupled with the future opening of Braulio Carrillo National Park, El Ceibo Sector, and rural tourism training by Tecnológico de Costa Rica, could be the beginning of this type of tourism in this community, helping to strengthen their productive activities and associative capabilities.
Proyecto de Graduación (Bachiller en Gestión del Turismo Rural Sostenible) Instituto Tecnológico de Costa Rica, Escuela de Idiomas y Ciencias Sociales, 2016
Keywords: Turismo ecológico; Desarrollo turístico